Correlates of Fear of Victimization Among College Students in Spain: Gender Differences and Similarities - León, Carmen M. (Journal of interpersonal violence, 2022)
Past studies that have analyzed fear of victimization using samples composed of men and women have most frequently controlled for the effect of gender. This study not only controls for the effect of gender, but also examines how the predictors of fear of victimization may vary across gender. To do so, separate regression models for men and women were estimated and the corresponding z tests were calculated for the purpose of analyzing whether the differences between genders were significant. The results showed that women scored higher on the general fear of crime victimization scale, as well as for fear of becoming victims of each of the specific crimes under study. Religiosity had an equally significant effect on men and women’s fear of victimization. Also, younger participants were more likely to fear being victims in the cases of both men and women, although this effect was even more pronounced among women. In addition, respondents’ fear of victimization differed across gender based on sexual orientation. Finally, the results showed a few variables (political orientation and sexual victimization) that were only significant in the case of women, but not of men. The findings of this study confirm that fear of victimization and its predictors vary between women and men.